ANALISIS RISIKO SAHAM PERUSAHAAN REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA - Indri Hafsari Gultom; Khaira Amalia Fachrudin (Jurnal Media Informasi Manajemen, 2013)
Abstract This research aims to determine and analyze the differences in systematic risk and unsystematic risk between the real estate and property sub-sector and building construction sub-sector ini The Indonesian Stock Exchange. This research is comparative research. Sampling techique using saturated samples with a total samples 51 companies, comprising 44 companies real estate and property sub-sector and 7 companies building construction sub-sector. This research uses secondary data. The analysis method used is descriptive analyze and statistical method,  independent sample t-test was used to analyze the differences in systematic risk and unsystematic risk between the real estate and property sub-sector and building construction. The results of this research indicate that there was no difference in systematic risk and unsystematic risk between the real estate and property sub-sector and building construction sub​​-sector with alpha 0.05. The implication of this research are investors can invest on both sub-sectors because there is no difference in systematic risk and unsystematic risk between of real estate and property sub-sectors and building construction sub-sectors.   Keywords: systematic risk, unsystematic risk, real estate and property sub-sector, building construction sub-sector.